Bridges on the digital divide - Caribbean initiatives for the information society - Sanatan, Roderick (Centre for International Services. UWI Cave HillBB, 2004)
Looks at innovations in education as well as sectoral innovation. Presents country case studies dealing with ICT policy and strategy change. Explores some sectoral regional experiences and possibilities.